Lingua-Cultural Analysis of Interrogative Sentences in English and Uzbek Languages (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Interrogative sentences are an essential aspect of any language, reflecting both linguistic structures and cultural nuances. This study investigates the lingua-cultural features of interrogative sentences in English and Uzbek languages, emphasizing their syntactic, semantic, and pragmatic aspects. The research explores how cultural contexts influence the formulation and use of interrogative constructions. By comparing these two languages, the study highlights both universal and language-specific features of interrogatives. The findings contribute to a deeper understanding of cross-linguistic communication and cultural pragmatics, which is particularly relevant for language learners and translators.